KETERAMPILAN GENERIK MAHASISWA PGSD PADA KONSEP SISTEM INDERA DENGAN MODEL PEMBELAJARAN JIGSAW BERMODIFIKASI Q CARD - Suci Siti Latifah; Fitri Siti Sundari (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
The aim of this research is to analyze students’ scientific generic skill using Jigsaw modified by Q Card on senses system concept. The research was conducted in three meetings. The sample is first semester students who learned about Basic Concept of Biology for primary teacher class A, B, C and D. Descriptive analysis method with non-test data collecting technique is used in this research. Based on the research result and discussion gained from observation sheet and test item, it can be concluded that students have scientific generic skill from the lowest to the highest respectively as follow; building concept (61.025) sufficient category, logical inference (64.175) sufficient category, cause and effect (65.175) sufficient category, indirect observation (71.65) good category, symbolic language (77.475) good category and the highest is mathematic modeling (77.75) good category. Positive response is showed by some of the students on teaching learning process using Jigsaw modified by Q Card. The lowest response is 74% on the category of exercising.